2018
DOI: 10.1371/journal.pone.0191834
|View full text |Cite|
|
Sign up to set email alerts
|

Enterohemorrhagic Escherichia coli O157 subclade 8b strains in Chiba Prefecture, Japan, produced larger amounts of Shiga toxin 2 than strains in subclade 8a and other clades

Abstract: Enterohemorrhagic Escherichia coli O157 (O157) strains can be classified into clades (one of several phylogenetic groups) by single nucleotide polymorphisms (SNPs): these are clade 1, clade 2, clade 3, descendant and ancestral clades 4/5, clade 6, clade 7, clade 8, clade 9, and clade 12. Some recent studies showed that some O157 strains in clade 8 produced a larger amount of Shiga toxin (Stx) 2 than other strains. In this study, 1121 epidemiologically unlinked strains of O157 isolated in Chiba Prefecture, Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(101 reference statements)
1
6
0
Order By: Relevance
“…Our results also corroborated the previous finding that clade 8 should be divided into two groups [ 4 , 5 , 12 ]. Clade 8 has been thought to have an important genotype because of its high likelihood of causing HUS [ 5 , 6 , 7 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results also corroborated the previous finding that clade 8 should be divided into two groups [ 4 , 5 , 12 ]. Clade 8 has been thought to have an important genotype because of its high likelihood of causing HUS [ 5 , 6 , 7 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study indicated that clade 7 includes two lineages, which are phylogenetic groups, and those lineages were redefined as separate clades, namely, clades 7 and 12 ( Supplementary Table 1 ) [ 3 , 15 ]. However, our subsequent studies [ 4 , 5 ] showed that clade 7 could be further divided into several clades. Clade 8 has also been reported to be divided into two groups [ 4 , 5 , 12 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the USA, clade 8 strains have been associated with more severe human disease, which led researchers to define it as hypervirulent [18]. Although clade 8 strains had higher Stx2a expression levels relative to strains from other clades, along with unique genetic features [11,21,22], to date the factors associated with the increased virulence and Stx2a production are not completely understood. Interestingly, the clade 8 EHEC O157:H7 isolates obtained from bovines in Argentina had a certain degree of genetic variability and displayed variable virulence in in vitro and in vivo assays [20].…”
Section: Introductionmentioning
confidence: 99%